A Grammar of Bunaq - Schapper, Antoinette (Mouton grammar library ;, 2022)
This is a comprehensive grammar of the Papuan language Bunaq as spoken in the district of Lamaknen. Bunaq belongs to the Timor-Alor-Pantar language family, which comprises the westernmost Papuan languages. Surrounded on all sides by Austronesian languages, Bunaq has developed in isolation from other members of the family, and as a result shows a range of unique morphosyntactic patterns. This grammar provides a detailed synchronic description of Bunaq based on a functional-typological approach. Following additional fieldwork and containing new material and analyses, this book is a thoroughly revised version of the author's 2010 PhD thesis, which won the Pāṇini Award of the Association for Linguistic Typology.